A note on the type of the name Rhizobotrya alpina (Brassicaceae) - Villani, Mariacristina; Marcucci, Rossella; Peruzzi, Lorenzo (Phytotaxa, 2015)
This study is related to the project “The Italian loci classici census”, ongoing since 2010 (Domina et al. 2012, Peruzzi et al. 2015). During the analysis of systematic and nomenclatural aspects of the species involved, some difficulties related to the identification of type localities have been pointed out. Our contribution has the aim to clarify the nomenclatural history of Rhizobotrya alpina Tausch (1836: 34).